Economic expansion of China in Ukraine. Can the New Silk Road project support Ukrainian statehood? - Wojcieszak, Łukasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The purpose of this paper is to present the current condition of Ukrainian-Chinese economic relations, in particular initiatives related to the New Silk Road project. The author describes the main areas of cooperation between China and Ukraine, the results of individual initiatives, as well as the difficulties faced by some areas of bilateral cooperation. China turns out to be essential for Ukraine in a period when its relations with Russia have deteriorated and the European Union cannot provide Ukraine with sufficient support.
Keywords: Ukraine; China; economy; New Silk Road; statehood